The Ability to Acquire Iron Is Inversely Related to Virulence and the Protective Efficacy of Francisella tularensis Live Vaccine Strain - Fletcher, Joshua R.; Crane, Deborah D.; Wehrly, Tara D.; Martens, Craig A.; Bosio, Catharine M.; Jones, Bradley D. (Frontiers in Microbiology, 2018)
Francisella tularensis is a highly infectious bacterial pathogen that causes the potentially fatal disease tularemia. The Live Vaccine Strain (LVS) of F. tularensis subsp. holarctica, while no longer licensed as a vaccine, is used as a model organism for identifying correlates of immunity and bacterial factors that mediate a productive immune response against F. tularensis. Recently, it was reported that two biovars of LVS differed in their virulence and vaccine efficacy. Genetic analysis showed that they differ in ferrous iron homeostasis; lower Fe2+ levels contributed to increased resistance to hydrogen peroxide in the vaccine efficacious LVS biovar. This also correlated with resistance to the bactericidal activity of interferon γ-stimulated murine bone marrow-derived macrophages. We have extended these findings further by showing that a mutant lacking bacterioferritin stimulates poor protection against Schu S4 challenge in a mouse model of tularemia. Together these results suggest that the efficacious biovar of LVS stimulates productive immunity by a mechanism that is dependent on its ability to limit the toxic effects of oxidative stress by maintaining optimally low levels of intracellular Fe2+.